2020
DOI: 10.1177/2333794x20947926
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patients in a Local Nepali Emergency Department: Presenting Complaints, Triage and Post-Discharge Mortality

Abstract: Background. In low-income countries, pediatric emergency care is largely underdeveloped although child mortality in emergency care is more than twice that of adults, and mortality after discharge is high. Aim. We aimed at describing characteristics, triage categories, and post-discharge mortality in a pediatric emergency population in Nepal. Methods. We prospectively assessed characteristics and triage categories of pediatric patients who entered the emergency department (ED) in a local hospital. Patient house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…15 The mortality rate was highest among patients with sepsis, according to studies done in Uganda and Mozambique's intensive care units, 16,17 while a study done in Nepal found that post-discharge mortality among children with infections was higher. 18 Vasoactive medication use was found to be a predictor of mortality in a research from Rwanda. 19 Death before discharge is a rare event in modern nations.…”
Section: Introductionmentioning
confidence: 94%
“…15 The mortality rate was highest among patients with sepsis, according to studies done in Uganda and Mozambique's intensive care units, 16,17 while a study done in Nepal found that post-discharge mortality among children with infections was higher. 18 Vasoactive medication use was found to be a predictor of mortality in a research from Rwanda. 19 Death before discharge is a rare event in modern nations.…”
Section: Introductionmentioning
confidence: 94%